(untitled) (Revista História & Perspectivas, 2010)
A partir da metodologia da História Oral e Memória, foi possível analisar as relações de sociabilidade de mulheres que dividem suas ocupações entre os afazeres domésticos, a família e a vida no meretrício. O contexto histórico, desenrolado numa Zona de Baixo Meretrício na cidade de Tianguá-Ceará - fechada no ano de 2002, pelo Juizado da Infância e Juventude -, nos permite trazer à tona o viver e o conviver na família das meretrizes. PALAVRAS-CHAVE: História Oral. Família. Cotidiano. ABSTRACT: From the methodology of Oral History and Memory, it was possible to analyze the relations of sociability of women who divide its occupations between the domestic tasks, the family and the life in the prostitution. The historical context, uncurled in a Zone of Low Prostitution in the city of Tianguá-Ceará - closed in the year of 2002, for the Court of Infancy and Youth - in allows them, to bring to tona, the life and coexisting in the family of the prostitutes. KEYWORDS: Oral History. Family. Daily.